IT OUTSOURCING AS A STRATEGIC DIRECTION FOR THE DEVELOPMENT OF UKRAINE'S ECONOMY ON ITS PATH TO SUSTAINABLE DEVELOPMENT - Korolchuk, L.V. (The actual problems of regional economy development, 2023)
The article raises the issue of the need to determine the strategic directions of the development of Ukraine’s economy on the eve of the development and implementation of the post-war recovery plan of our country, which will become a powerful catalyst for the development of the most promising industries thanks to the financial support of our international partners and russian reparations. With the help of statistical analysis, as well as the analysis of scientific and reference literature on the mentioned issues, the expediency of considering the field of IT outsourcing as a priority in the current conditions in the context of the concept of sustainable development, the general character of which for Ukraine is declared in international and national strategic documents, is substantiated. Ukrainian outsourcing companies are noted for their high recognition and competitiveness on the global and Eastern European markets in particular. This area turned out to be the most stable and adaptable in war conditions, since such a business is functional even without stationary equipment, and if there is an Internet connection, it is possible to work remotely from any place. IT outsourcing belongs to the science-intensive spheres of the economy, does not involve the consumption of natural non-renewable resources, provides jobs for highly qualified specialists with decent pay for their work, is a source of currency for the country, is designed to improve working conditions and the standard of living of the population as a whole, and therefore meets the goal of sustainable development. Based on the methods of scientific abstraction, idealization and observation, the relationship between the development of IT outsourcing and the Sustainable Development Goals was investigated. The strategic planning algorithm is defined by the strategic analysis method, during which a SWOT analysis of IT outsourcing was carried out as a sphere of the Ukrainian economy on its way to sustainable development and, as a result of the quantitative ratio of strengths, weaknesses, as well as opportunities and threats, the optimal strategy was chosen for development of this field among potentially possible ones. Prospects for further research on this topic in the direction of developing programs and road maps as part of the implementation of the proposed strategy have been determined.